Analisis Peranan Ekonomi Digital dalam Meningkatkan Pendapatan Pelaku Usaha Mikro Kecil Menengah (UMKM) di Indonesia - Yolanda Widya Anggreni Situmorang; Bakhtiar Efendi; Lia Nazliana Nasution (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to evaluate the extent to which the digital economy plays a role in increasing the income of Micro, Small and Medium Enterprises (MSMEs) in Indonesia. This research methodology is quantitative with the Two-Stage Least Squares (TSLS) approach. The variables analyzed include capital, interest rates, inflation, the use of electronic money (e-money), and Gross Domestic Product (GDP). The results reveal that e-money utilization and GDP growth have a significant positive influence on increasing MSME income. In contrast, inflation has a negative impact. The model that includes e-money and inflation variables has the highest R-squared value, indicating a strong explanatory ability of the income variable. These findings reinforce the importance of digital literacy and economic stability as key supporting factors in optimizing the potential of the digital economy for MSME players.